Serum and tissue markers of myopathy in patients with colorectal cancer - Nicoletta Adami (PAGEPress Publications, 2012)
Skeletal muscles in patients with cancer undergo many changes due to immuno-inflammatory factors of tumor origin, or to chemotherapy and irradiation. Aim of the present study is to identify serological biomarkers and early myopathic features in skeletal muscle biopsies from weight stable patients bearing colorectal cancer at the onset of disease. Morphometric analyses by histochemistry and immunohistochemistry were performed on intraoperative muscle biopsies from patients with early colorectal cancer and from weight stable patients undergoing surgery for benign non-inflammatory conditions. Serological analyses for testing markers of inflammation (C Reactive Protein, CRP), muscle enzymes, (Creatin Kinase, CK), soluble isoforms of adhesion molecules (Neural Cell Adhesion Molecule, NCAM), and a marker of protein turnover (prealbumin, a typical indicator of caloric and protein malnutrition) were also performed. Fifty oncologic patients (28 male/22 female) and 25 non oncologic patients (18 male/7 female) (p=N.S.) were studied. In muscles from cancer patients we observed a subclinical myopathy characterized by an abnormal distribution of myonuclei. The percentage of myofibers with internalized nuclei was significantly higher in oncologic (median= 13.1%, IQR= 6.0-20.3) than in non oncologic patients (median= 3%, IQR= 2.5-6.1) (p<0.0001). The frequency of these internally nucleated myofibers is even higher in a subgroup of oncologic patients taking myotoxic drugs. In cancer patients, we observed an inverse correlation between the number of internally nucleated fibers and the presence of node metastasis (N+) (ρ)=-0.30 (p=0.03). Moreover, in patients with colorectal cancer, low serum levels of preoperative prealbumin (median= 167,7 mg/L, normal range 200-400 mg/L), were detected. The link between the observed early myopathy and long-term cachexia is supported also by the altered expression of sarcolemma associated proteins, in particular laminin and dystrophin. Patients affected with colorectal cancer at disease onset display low pre surgical serum levels of prealbumin (also known as transtiretin) and regenerating myofibers in the rectus abdominis muscle. The myopathy appears to be associated with an early stage of cancer and it could be interpreted as a consequence on the skeletal muscle of anti-cancer defense mechanisms (pro- apoptotic, thus non inflammatory), during the pre-invasive stage of the neoplasia. A comprehensive study on the potential molecular mechanisms that are responsible for this cancer-associated myopathy could possibly provide new diagnostic and prognostic biomarkers and new therapeutic targets to prevent the severe loss of muscle tissue which characterizes late-onset cancer cachexia.